2022
DOI: 10.1007/s00330-021-08470-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiographers’ actions and challenges when confronted with inappropriate radiology referrals

Abstract: Objectives To explore radiographers’ actions toward inappropriate referrals and hindrances to assessing referrals. Methods An online survey was distributed to radiographers via the International Society of Radiographers and Radiological Technologists (ISRRT) networks. The questionnaire consisted of 5-point Likert scale questions on radiographers’ actions to supplement referral information, actions for unjustified referrals and hindrances to referral assessment. The ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This implied that when radiologists received detailed information about the patient during the consultation process, they could generate a more credible and trustworthy radiological report that can safeguard the patients from misdiagnosis and treatment. Previous research work confirmed that the acts of radiographers in completing missing data during radiology referrals enhance the provision of high-quality medical services [ 32 ]. However, in some of the referral consultations, radiologists were unable to access the patient to obtain the information they missed because the patient’s family or caregivers were responsible for transporting the image during the consultation process [ 50 , 53 ].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This implied that when radiologists received detailed information about the patient during the consultation process, they could generate a more credible and trustworthy radiological report that can safeguard the patients from misdiagnosis and treatment. Previous research work confirmed that the acts of radiographers in completing missing data during radiology referrals enhance the provision of high-quality medical services [ 32 ]. However, in some of the referral consultations, radiologists were unable to access the patient to obtain the information they missed because the patient’s family or caregivers were responsible for transporting the image during the consultation process [ 50 , 53 ].…”
Section: Discussionmentioning
confidence: 94%
“…Findings showed that only 30% of the radiographic images could be correctly interpreted by physicians and students due to a lack of adequate knowledge [ 57 ]. As a solution, enhancing the skills of consulting clinicians working at distant hospitals through short-term training is recommended [ 32 , 57 59 ]. To further reduce medical errors, it is advised that quick consultation of medical images in quest of expert judgment is essential [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of request orders may well impact on the quality of a novice radiographer's work with regard to decisions concerning patient positioning, imaging projections, exposure parameters and dose optimization, which could affect the selection of imaging protocols for patient safety and the accuracy of image interpretation and radiology reports. 24,25 In addition to drawing on prior experience and knowledge through reflection, study participants valued an efficiently and effectively functioning team following the standard care processes needed for sound medical imaging outcomes for patients without compromising staff and patient safety. 24,26 Participants also shared examples that illustrated the importance of coordinating activities, communicating through collaboration, and endeavouring to participate in negotiation and shared decision making.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 Participants also shared examples that illustrated the importance of coordinating activities, communicating through collaboration, and endeavouring to participate in negotiation and shared decision making. 24,25,27 Interpersonal and professional relations were developed by building rapport and engaging with the team both within the radiography department and beyond. 28 According to Chipere et al, positive interpersonal interactions are the cornerstone of creating a workplace where RGRs feel comfortable about broadening their experience and sense of empowerment.…”
Section: Discussionmentioning
confidence: 99%